Application of Association Rule Method Using the ECLAT Algorithm on Over-the-Counter Drug Transaction Data at Pharmacy “X” - Dini, Sekti Kartika; Fuadah, Sekar Ridho (Jurusan Matematika FMIPA UNM, 2025)
Health is a fundamental need for every human being that plays an important role in improving the quality of life and productivity of society. As one of the means of pharmaceutical services, pharmacies not only serve as places for drug distribution but also as abundant sources of information regarding community purchasing patterns for health products. In the current digital era, every transaction that occurs at a pharmacy generates high-value data that can be utilised for data-driven decision making. One of the relevant analytical approaches in this context is Market Basket Analysis (MBA). Association rule is a commonly used method in MBA. This method generates rules in the form of implications